2006
DOI: 10.1158/1055-9965.epi-06-0176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mammography on Breast Cancer Risk in Women with Mutations in BRCA1 or BRCA2

Abstract: Women who carry mutations in either the BRCA1 or BRCA2 genes are at risk for early-onset breast cancer and are recommended to begin screening mammography at age 25 to 30 years. Results of in vitro and animal studies suggest that BRCA1/BRCA2 mutation carriers are hypersensitive to ionizing radiation and possibly to radiationinduced breast cancer. This study was undertaken to investigate the association of low-dose radiation exposure from mammograms with breast cancer status in BRCA mutation carriers. One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
1
37
2
Order By: Relevance
“…Since IR is a risk factor of breast cancer (Goss and Sierra, 1998), and our data implies that BRCA1 carriers may be more susceptible to IR-induced tumor, a safety concern on repeated screening mammography for Brca1 carriers is raised. Recently, several large-scale studies concluded that screening mammography is not associated with a significantly increased risk of cancer formation in Brca1 carriers (Goldfrank et al, 2006;Narod et al, 2006). Hence, a small dose of radiation used for diagnostic Figure 1 Survival curves of Brca1 þ /À and þ / þ (wild-type) mice that received a single dose of whole-body gamma radiation (0, 2.5 or 5.0 Gy) at the age of 5-6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Since IR is a risk factor of breast cancer (Goss and Sierra, 1998), and our data implies that BRCA1 carriers may be more susceptible to IR-induced tumor, a safety concern on repeated screening mammography for Brca1 carriers is raised. Recently, several large-scale studies concluded that screening mammography is not associated with a significantly increased risk of cancer formation in Brca1 carriers (Goldfrank et al, 2006;Narod et al, 2006). Hence, a small dose of radiation used for diagnostic Figure 1 Survival curves of Brca1 þ /À and þ / þ (wild-type) mice that received a single dose of whole-body gamma radiation (0, 2.5 or 5.0 Gy) at the age of 5-6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also examined whether mammography-associated radiation was related to an increased risk of breast cancer (32)(33)(34)(35)(36)(37). In contrast to the doses of radiation delivered to the contralateral breast during RT, the average radiation dose received during a mammogram (average ≤ 0.01 Gy) is lower by more than two orders of magnitude (2).…”
Section: Discussionmentioning
confidence: 99%
“…Because BRCA mutations are associated with a reduction in DNA repair efficiency [3], it has been hypothesized that BRCA1/2 mutation carriers might experience greater risk of radiation-induced breast cancer. In two recent studies, exposure to chest X-rays, especially at young ages, was associated with an increased breast cancer risk among carriers [4,5], but in two other studies on exposure to mammograms no association was observed [6,7]. However, these results must be interpreted with caution since the studies relied on self-reported diagnostic radiation history and had a retrospective design (with potential recall and/or survival bias).…”
Section: Introductionmentioning
confidence: 91%
“…However, these results must be interpreted with caution since the studies relied on self-reported diagnostic radiation history and had a retrospective design (with potential recall and/or survival bias). In the Netherlands, carriers are currently recommended to start breast cancer screening by MRI from age 25 and mammography from age 30 onwards [8], but in the past carriers may have started mammographic screening at younger ages [6,7].…”
Section: Introductionmentioning
confidence: 99%